Efektivitas Digital Marketing LinkedIn Ads dan Email Blast untuk Meningkatkan Partisipasi Webinar Mappable - Syawalido, Luky; Widodo, Suprih (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
This study aims to analyze the effectiveness of LinkedIn Ads and Email Blast as digital marketing strategies to increase participation in the Mappable webinar organized by PT. Indi Teknokreasi Internasional. The findings reveal that LinkedIn Ads excel at reaching new professional audiences by leveraging features such as Sponsored Content, Message Ads, and Lead Gen Forms, which allow targeting based on job titles, industries, and locations. A total of 32.8% of respondents reported learning about the webinar through LinkedIn, indicating the platform's relevance as a primary information channel for professional audiences. Meanwhile, Email Blast demonstrates high effectiveness in converting existing audiences into webinar participants. Data analysis from eight audience segments recorded performance variations in open rates, click rates, and bounce rates, highlighting the importance of segmentation and content personalization. The combination of LinkedIn Ads and Email Blast provides significant synergy, with LinkedIn Ads expanding the reach to new audiences while Email Blast optimizes conversions through more targeted messaging. This study recommends validating email recipient databases, optimizing delivery times, and utilizing analytics to enhance future campaign effectiveness. With this integrated approach, both strategies are proven to significantly boost engagement and participation in webinars.